Financial Innovations Risk, Financial Distress and Firms Value: A Critical Review of Literature - Ndicu, Ndua Daniel (European Scientific Journal, ESJ, 2018)
Throughout history, society has always sought for ways and means of responding to life challenges and opportunities. Several scholars support the need for innovation for a firm to remain a good performer during its existence, though the level of risks associated with this kind of undertaking has not received the coveted attention. With the use of financial innovations companies can safely utilize current or go for more risky and up to date technologies that can have a drastic and positive impact on their ventures. Additionally, financial innovations have had a tremendous impact in enriching finance and enhancing the economic prosperity of many firms. However, this financial innovation may also be ruinous to the organization if it is overboard. This study thus sought to review the extant theoretical and empirical literature relating to risky financial innovations, financial distress and firm value. Specifically the study was guided by the following objectives: To review extant theoretical literature on the constructs of risky financial innovations, financial distress and firm value; to review past empirical literature on the constructs of risky financial innovations, financial distress and firm value; to identify the emerging theoretical and empirical gaps that form the basis of future research. Additionally, the study sought to propose a theoretical model to respond to the identified gaps. The study has concluded that financial innovation has positive impact on financial performance and firm value, there is direct relationship between financial innovation and financial deepening and financial innovation enhances growth of the firm.